Do Non-monetary Interventions Improve Staff Retention? Evidence from English NHS Hospitals - Melisa Sayli; Giuseppe Moscelli; Jo Blanden; Chris Bojke; Marco Mello (Institute of Labor Economics (IZA), 2022)
Excessive turnover reduces the stock of an organization's human capital. In the public sector, where wage increases are often constrained, managers need to leverage non-monetary working conditions to retain their workers. We investigate whether workers are responsive to improvements in non-wage aspects of their job by evaluating the impact on nurse retention of a programme that encouraged public hospitals to increase staff retention through data monitoring and improving the non-pecuniary aspects of nursing jobs. Employing rich employee-level administrative data from the universe of English NHS hospitals, and a staggered difference-in-difference design, we find that the programme has improved nursing retention within hospitals and decreased exits from the public hospital sector. Our results indicate that a light-touch intervention can shift management behavior and improve hospital workforce turnover. These findings are important in sectors affected by labor supply shortages, and they are especially policy-relevant in the health care context, where such shortages have potentially negative effects on patient outcomes.
Keywords: J32; J38; J45; J63; I11; C22; 330; labor supply; workforce retention; non-monetary incentives; hospital care; staggered difference-in-differences